2020
DOI: 10.1021/acsomega.0c00896
|View full text |Cite
|
Sign up to set email alerts
|

Acacia Xylan as a Substitute for Commercially Available Xylan and Its Application in the Production of Xylooligosaccharides

Abstract: Over the past two decades, birchwood and beechwood xylans have been used as a popular substrate for the characterization of xylanases. Recently, major companies have discontinued their commercial production. Therefore, there is a need to find an alternative to these substrates. Xylan extraction from Acacia sawdust resulted in 23.5% (w/w) yield. The extracted xylan is composed of xylose and glucuronic acid residues in a molar ratio of 6:1 with a molecular mass of ∼70 kDa. The specific optical rotation analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 51 publications
(124 reference statements)
0
12
0
1
Order By: Relevance
“…The greatest activity (5230 U/ml) was observed with beechwood xylan, which contains β-1,4 linkages between D-xylose residues 70 . The residual activity was 7.2% for pectin.…”
Section: Resultsmentioning
confidence: 99%
“…The greatest activity (5230 U/ml) was observed with beechwood xylan, which contains β-1,4 linkages between D-xylose residues 70 . The residual activity was 7.2% for pectin.…”
Section: Resultsmentioning
confidence: 99%
“…However, the obtained results seem to be influenced by the demineralization procedure. Sharma et al 253 revealed that alkali lignin washed with hydrochloric and nitric acids produced more char and less condensable fraction than the raw sample. Conversely, alkali lignin samples washed with hydrofluoric acid produced a slightly lower char yield despite the reduction of the ash content.…”
Section: Effect Of Inherent Metals On Pyrolysis Processmentioning
confidence: 99%
“…The hemicellulose of SB contains 55.2 (%, w/w) xylose and 10.7 (%, w/w) arabinose of the total hemicellulose content . The enzyme xylanase (endolytically) and xylosidase (exolytically) act on the main chain of xylan polysaccharides. The use of accessory enzymes, such as α- l -arabinofuranosidase, to hydrolyse side chains synergistically acts and enhances the rate of overall hydrolysis and increases the production of monosaccharides . The monosaccharides, arabinose, and xylose act as antiglycemic agents and are of immense importance to the human health.…”
Section: Introductionmentioning
confidence: 99%
“…The monosaccharides, arabinose, and xylose act as antiglycemic agents and are of immense importance to the human health. These monosaccharides can be fermented in the food industry for the production of xylitol and arabitol or in fuel industries for enhanced bioethanol production. , The aim of this study was to facilitate the saccharification of the xylan portion of hemicellulose by including an additional enzyme, α- l -arabinofuranosidase, along with xylanase and xylosidase of sugarcane waste and achieve enhanced TRS yield by optimizing the various conditions of the process. The pretreatment conditions were optimized to reduce the hemicellulose loss during pretreatment.…”
Section: Introductionmentioning
confidence: 99%